Mrs. McNosh and the great big squash - Weeks, Sarah; Westcott, Nadine Bernard ([New York, N.Y.] : HarperFestival, 2000)
After planting a squash, Mrs. McNosh watches as it grows as big as a house and later finds a use for it.
"A Laura Geringer book."
"Harper growing tree"--Cover.
"For ages 3 and up"--Cover.
Accelerated Reader AR
Keywords: Squashes -- Fiction; Vegetables -- Fiction; Gardens -- Fiction; Humorous stories; Stories in rhyme